Esophageal perforation following bite of inner tube of automobile tyre: An unusual cause of barotrauma - Kadian Y; Agarwal S; Rattan K; Nityasha (Wolters Kluwer Medknow Publications, 2010)
An 8-year-old child presented with severe chest pain and respiratory distress after he accidentally bit an automobile tyre tube which burst into his mouth. The chest radiograph revealed left-sided pneumothorax. Both esophagogram and computed tomogram (CT) scan revealed a perforation of the distal third of esophagus with extravasation of contrast on left side. The patient was treated conservatively with gastrostomy feeds and antibiotics for 5 weeks with a good response.